Preference Phenotypes in Support of Shared Decision–Making at Point‐of‐Care for Patients With Rheumatoid Arthritis: A Proof‐of‐Concept Study. Issue 5 (8th April 2019) - Hsiao, Betty; Binder‐Finnema, Pauline; Nowell, W. Benjamin; Michel, George; Wiedmeyer, Carole; Fraenkel, Liana
Abstract : Objective: In this proof‐of‐concept study, we sought to evaluate whether a value clarification tool enabling patients to view a set of rheumatoid arthritis (RA) treatment preference phenotypes could be used to support shared decision‐making at the point‐of‐care. Methods: We conducted a pretest/post test study. English‐speaking patients with RA presenting to their scheduled outpatient visits were asked to participate. Visits for patients with active RA were transcribed. Shared decision‐making components were measured using a quantitative coding scheme based on an established model of shared decision‐making. Results: Forty‐six visits were included in the pretest and 40 in the post test phases. Providers offered more disease‐modifying antirheumatic drugs (DMARDs) (2 or more) in the post test visits (60%) compared to the pretest visits (47.8%). Overall, more patients vocalized their values and/or preferences in the post test visits compared to the pretest visits for treatment escalation decisions including a choice of 1 new DMARD (90.9% versus 56.3%), 2 or more new DMARDs (95.8% versus 86.4%), as well as prednisone (87.5% versus 66.7%). Providers were also more likely to base their recommendations on patients' values and/or preferences in the post test (100% of 6 visits) than the pretest (64.3% of 14 visits) phases during visits in which a recommendation was made. The mean ± SD length of the visit was 29.9 ± 11.6 minutes and 25.1 ± 10.7 minutes in the pretest and post test phases, respectively. Conclusion: This study provides an early indication that a value clarification tool allowing patients to consider a set of preference phenotypes can support shared decision‐making at the point‐of‐care without extending visit time.